Genuine Purity of Blood: The 2019 Report on Investor Citizenship and Residence in the European Union and its Litigious Progeny - Dimitry Kochenov (London School of Economics and Political Science (LSE), European Institute, 2020)
This article provides a brief critical assessment of the European Commission's January 2019 'Report on Investor Citizenship and Residence Schemes in the European Union'. Since it is the first detailed document by the Commission outlining this institution's position on the matters of investment residence and citizenship, and given the Commission's recently articulated intentions to bring Cyprus and Malta to Court over their investment migration law and practice, the Report in question is of paramount importance. The document sets the legal-political context of the regulation of the migration of wealthy third-country nationals in Europe. It is also deeply flawed. Rather that summarising the document, this article focuses on five core deficiencies of the Commission's embarrassing product and demonstrates how the Commission failed to get the EU's own law right, in addition to showing poor understanding of international law on the matter. Ripe with nationalist assumptions not rooted in the Treaties or the secondary law of the Union and showcasing a timid, convoluted and inconsistent analysis of the issues it purports to address, the Report has unsurprisingly failed to change the landscape of regulation in the field of investment citizenship and residence in the EU or anywhere else in the world. What it did make clear, however, was that the mere political suspicion of a particular type of naturalisation is enough for the European Commission to set aside the law and misinform the public, underlying once again the problematic tension between the growing political nature of this institution and its key task as guardian of the Treaties. There is a burning need for the Commission to take a more careful, coherent and informed approach to its actions, an approach indispensable for the preservation of the rule of law in the Union.
Keywords: 330; CBI; citizenship by investment; RBI; residence by investment; investment migration; rule of law